Primary thyroglossal duct carcinoma with lateral neck metastasis in an adolescent girl - Papendieck, Patricia (2018)
Thyroglossal duct cysts are the most common thyroid developmental anomalies accounting for 75% of midline neck tumors in children. Carcinomas arising fromthis remnant are very rare in adults and even scarcer in pediatrics. Preoperative diagnosis is a challenge and appropriate treatment is controversial. We report the caseof a 13-year-old adolescent girl with a growing midline neck mass suspicious for a thyroglossal duct cyst who underwent a Sistrunk procedure. Histologic analysisrevealed the presence of a papillary carcinoma in the wall. She completed treatment with total thyroidectomy and radioactive iodine. Postablative whole body scanshowed an inferior neck metastasis. We discuss previous pediatric cases of this entity and the different options in the management strategy.